Antigen-specific T cell responses to BK polyomavirus antigens identify functional anti-viral immunity and may help to guide immunosuppression following renal transplantation - Chakera, A; Bennett, S; Lawrence, S; Morteau, O; Mason, P; O'Callaghan, C; Cornall, R (2011)
Infection with the polyoma virus BK (BKV) is a major cause of morbidity following renal transplantation. Limited understanding of the anti-viral immune response has prevented the design of a strategy that balances treatment with the preservation of graft function. The proven utility of interferon-gamma enzyme-linked immunospot (ELISPOT) assays to measure T cell responses in immunocompetent hosts was the basis for trying to develop a rational approach to the management of BKV following renal transplantation. In a sample of transplant recipients and healthy controls, comparisons were made between T cell responses to the complete panel of BKV antigens, the Epstein-Barr virus (EBV) antigens, BZLF1 and EBNA1, and the mitogen phytohaemagglutinin (PHA). Correlations between responses to individual antigens and immunosuppressive regimens were also analysed. Antigen-specific T cell responses were a specific indicator of recent or ongoing recovery from BKV infection (P<0·05), with responses to different BKV antigens being highly heterogeneous. Significant BKV immunity was undetectable in transplant patients with persistent viral replication or no history of BKV reactivation. Responses to EBV antigens and mitogen were reduced in patients with BKV reactivation, but these differences were not statistically significant. The T cell response to BKV antigens is a useful and specific guide to recovery from BKV reactivation in renal transplant recipients, provided that the full range of antigenic responses is measured. © 2011 The Authors. Clinical and Experimental Immunology © 2011 British Society for Immunology.